2018
DOI: 10.3928/1081597x-20180402-03
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Epithelial Remodeling After Standard Epithelium-off Corneal Cross-linking in Keratoconic Eyes

Abstract: Epithelium-off CXL resulted in modest regularization of the epithelial thickness profile across the central 5 mm of the cornea at 6 months. This could slightly mask flattening of the underlying stroma. [J Refract Surg. 2018;34(6):408-412.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…24 The data presented here show epithelial thickening at month 1 after crosslinking, followed by a subsequent return to baseline values. This is consistent with other previous reports 25 and explains the transient increase in Kmax at month 1.…”
Section: Discussionsupporting
confidence: 94%
“…24 The data presented here show epithelial thickening at month 1 after crosslinking, followed by a subsequent return to baseline values. This is consistent with other previous reports 25 and explains the transient increase in Kmax at month 1.…”
Section: Discussionsupporting
confidence: 94%
“…At 6 months after C-CXL, a statistically signi cant improvement in epithelial irregularity indices (SD by -1.31 µm and min-max by 5 µm) together with a thickening at the thinnest point (min:2.75 µm) was evident. Furthermore, Lautert et al [22] showed that the min-max epithelial thickness (from 24 ± 9 to 22 ± 9 µm), which is another index for epithelial uniformity, signi cantly decreased after C-CXL at 6 months in accordance with the results of our study (23 ± 9 to 18 ± 7 µm). In the current study, early after C-CXL (1 month), we observed a decrease (-2.55 to -4.75 µm) in epithelial thickness over the paracentral areas surrounding the cone, the maximum epithelial thickness being reduced by 6.25 µ and a reduction in the epithelial thickness standard deviations by 2.3 µm.…”
Section: Discussionsupporting
confidence: 92%
“…Lautert et al described a significantly decreased min-max value in ETM measured by SD-OCT at 6-month follow-up of their 93 KCN patients. The min-max parameter decrease strongly correlated with maximum keratometry readings on Scheimpflug imaging [ 126 ]. While a study using accelerated CXL by epithelium-off method (30 mW/cm2 for 4 minutes) found thinner CET in multiple nasal and inferior sectors and lower ETM SD in 12-month follow-up [ 127 ], others using transepithelial accelerated ETM could not find such changes in the same [ 128 ] or longer [ 129 ] follow-up periods.…”
Section: Etm In Corneal Diseasesmentioning
confidence: 99%